The Role of Culture in the Relationship Between Religiosity and Psychological Well-being - Lavrič, Miran (Journal of religion and health, 2008)
Several measures of religious practice and religious orientation (intrinsic/extrinsic/quest) and two measures of psychological well-being (positive affect and negative affect) have been employed in a cross-cultural survey of undergraduate university students from five different cultural/religious environments: Slovenia, Bosnia and Herzegovina, Serbia, the United States of America, and Japan. Results suggest that measures of exstrinsic, intrinsic, and quest religiosity are not entirely applicable in most of the cultures observed. Nevertheless, it was possible to discern abbreviated cross-culturally valid scales for each dimension. The strength and direction of the correlation between psychological well-being and a particular type of religious orientation proved to depend substantially upon culture. More importantly, the cultural environment plays a crucial role in shaping the relationship between general measures of religiosity and psychological well-being. According to the data, higher general levels of religiosity at the societal level are linked to more positive correlations between religiosity and psychological well-being. The overall picture leads to the conclusion that there is no culturally universal pattern in the relationship between measures of religiosity and psychological well-being and that the particular cultural and religious context should always be considered in studies dealing with this issue.